Impacts of supermarkets on child nutrition in China - Zhen Liu; Lukas Kornher; Matin Qaim (University of Bonn, Center for Development Research (ZEF), 2023)
In many developing countries, food environments are changing rapidly. One emblematic trend is the proliferation of supermarkets and other modern retailers. While changing food environments likely influence the types of foods supplied and consumed, research on the implications for people's diets and nutrition is still scant. Here, we analyze the effects of supermarkets on child diets and nutrition in China. We use nationally representative panel data that include information on households' access to supermarkets and individual-level anthropometric and dietary indicators. Results show that improved access to supermarkets leads to higher child dietary diversity and nutrient intakes, especially among children in rural areas and from low-income households. Supermarkets are also found to increase child height, but not weight. Estimates with different model specifications and placebo tests confirm the results' robustness. The effects are mediated through supermarkets contributing to more variety in local food supplies and lower average food prices. Our findings suggest that the spread of supermarkets improves child dietary quality and nutrition in China.
Keywords: Q18; I18; O10; 330; Food environments; Supermarkets; Child malnutrition; Dietary quality; Paneldata; China